OUTCLASS LANGUAGE LEARNING COMPARED TO PRESENTATION, PRACTICE, AND PRODUCTION TECHNIQUE TO TEACH SPEAKING - Hadi, Muhammad Zaki Pahrul; Miswaty, Titik Ceriyani; Syamsurrijal, Syamsurrijal (STKIP PGRI Ponorogo Press, 2022)
Speaking skill has been taught in every part educational institutes. This shows the importance of having good communication skill, especially in English. Teachers play very important roles in achieving the success of the students to use their oral language of English. Somehow, teachers often find difficulties in teaching such speaking skill. To overcome the teacher’s difficulty of finding the proper teaching techniques, Out-Class Language Learning is considered as an appropriate alternative strategy to teach speaking skill. It proposed great opportunities and rewards to both students and teachers. It gives many benefits in terms of fun, enjoyment, personal development, motivation and confidence. This article tries to describe and elaborate the concept of using Out-Class Language Learning to teach speaking skill. Presentation, Practice, and Production (PPP) technique is used to compare the OCLL technique.